Open surgical excision vs. endoscopic radiofrequency ablation in managing congenital pyriform sinus fistula—a comprehensive analysis of 166 cases - Xu, Mengrou; Chen, Wei; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2024)
Background Congenital pyriform sinus fistula (CPSF) is uncommon congenital abnormality, and the optimal definitive treatment has not yet been established. The aim of the present study was to comparatively evaluate patients with CPSF regarding the indications and outcomes of treatment with open surgical excision (OSE) versus endoscopic Radiofrequency Ablation (RA), and the advantages of both therapeutic procedures were also analyzed. Methods An observational, longitudinal, retrospective, analytical and comparative study was conducted on 166 consecutive pediatric patients with CPSF treated at Shanghai Children's Hospital between December 2018 and September 2023.Results In this study, there were 79 males and 87 females. The median age at operation was 4.8 years (8 days to 15 years). OSE and Endoscopic RA were respectively performed in 48 and 118 children. The gastric tube retention time after RA was longer (3 days vs 14 days) than after OSE. Patients with a history of incision and drainage (I&D) tended to choose OSE (75.0% vs. 39.0%, P＜0.01). There were no significant differences in postoperative complications and recurrence rates between these two groups (P＞0.05), but the hospitalization duration was shorter for RA group compared to OSE group [2(2-3) vs. 4(3-5), P＜0.01].Conclusions Both OSE and RA are recognized as first-line treatment options for CPSF, which show no significant differences in prognosis, except hospitalization duration and the gastric tube retention time.Nevertheless, the indications for OSE and RA differ, which are influenced by factors such as the inflammatory stage, specific typing, previous treatments, and the surgeon's expertise. The selection of surgical approach should be carefully determined based on individual circumstances.